The Effects of Family Ownership on Prices of Firms Announcing Bonus Issues - Norhamiza, Ishak (2012)
This study aims to investigate the effects of six governance characteristics on prices of firms announcing bonus issues. This study used a sample of 50 companies without other announcements. The six governance characteristics are family ownership, board size, proportion of independent directors, proportion of executive directors, proportion of family directors and board ownership while cumulative abnormal return from day -5 to day -1 is used as a proxy for the announcement effects. Market model and ordinary least squares (OLS) regression methods are used to examine the abnormal returns and the effects of corporate governance on abnormal returns. The findings showed proportion of family directors and proportion of executive directors have significant effect on cumulative abnormal return. This result indicates that investors reacted favourably to announcements by companies with a large proportion of either family directors or executive directors.